WHAT MIGHT HAVE BEEN - Johnson, A.G. (Scientia Militaria - South African Journal of Military Studies, 2012)
One of the most intriguing of mental pastimes is to ponder on what the result might have been if certain famous happenings had been reversed. For example, if the Spanish Armada had succeeded in its task; or if Hertzog had been successful in his revolt of 1914, but two happenings in quite recent history, both originated by Winston Churchill, make a fascinating study. In 1915, as First Lord of the Admiralty and a member of the War Cabinet, he persuaded his colleagues to stage an invasion of Turkey with a view to opening the Dardenelles and so linking up with Russia. This failed. In 1941 as Prime Minister and Minister of Defence, as soon as Germany invaded Russia, he proclaimed the latter an ally and promised her all the support and help the British Empire could give until victory was achieved. This succeeded.